Fotografias, narrativas e memórias sobre o lugar, a paisagem e o uso do solo na área de proteção ambiental Rota do Sol, Rio Grande do Sul - Gabriela Vitória de Oliveira; Aline Reis Calvo Hernandez; Patrícia Binkowski (Confins)
The research adopted the photograph as a resource to revisit individual and collective memories and to identify meanings that make up the place from the perception of the residents of the Environmental Protection Area (APA) Rota do Sol, Rio Grande do Sul, Rio Grande do Sul, Brazil (BR). The participants arranged their collections of photographs, which together with the narratives showed the perceptions and relations of belonging to the place, serving as a basis for understanding and interpreting the meanings that make up the place. In this way we take the photograph as a device of narratives and, in the light of the iconology, we carried out a discussion about the memory and the relevance meanings brought by the participants in 2 macro themes: Araucária: a symbolic meaning associated with affections, emotions and memory (3.1) and Changes in land use influencing production, work and social organization (3.2). To support the discussions we start with the theoretical-epistemological study of the use of photography as a research tool and memory device, as well as exploring the concept of landscape. The study allowed us to understand the relationships that bind people to the place, the forms of production, work and social organization, through data from the collective memory not previously analyzed.The use of photography made it possible to gather information that goes far beyond the objective plan in the printed image, allowing to explore and analyze the implicit and subjective aspects and to recognize important meanings to the local community.